SUSTAINABLE DEVELOPMENT OF RURAL TERRITORIES OF UKRAINE UNDER DECENTRALIZATION CONDITIONS, ENSURING THEIR CAPACITY - Cherniatina , V. A (Theory and Practice of Public Administration, 2021)
Rural territories are presently in the focus of attention, being characterized by the most acute socio-economic problems. This category sometimes includes territories with a highly developed economic potential that for certain reasons found themselves in the midst of a grave crisis, which can be proved by their high unemployment rate, a low level of economic entities’ investment activity, and a series of social problems. Thus, the question now arises as to introduction of comprehensive programs, reformation of rural economic development, and a search for various approaches to this urgent problem solution. The problems of an organizational and legal mechanism for state regulation of rural territories development have been elucidated in the works by many scientists. Yet, this subject remains understudied requiring further elaboration. The paper objective is to identify the problems of the legal support for rural territories development and possible ways to address them. Rural territories as socio-economic systems need to be managed by the state. The impact of the state on rural territories is exerted through administrative-regulatory functions of the state policy which is fixed in the appropriate normative and legal acts, elaborated state and regional development strategies, a variety of adopted and implemented programs, and in regulatory and administrative functions performed by public authorities.